2002
DOI: 10.1074/jbc.m112100200
|View full text |Cite
|
Sign up to set email alerts
|

5′-,3′-Inverted Thymidine-modified Antisense Oligodeoxynucleotide Targeting Midkine

Abstract: Oligodeoxynucleotides modified at both 5-and 3-ends with inverted thymidine (5-,3-inverted T) were introduced as new reagents for antisense strategies. These modifications were performed to make the oligodeoxynucleotides resistant to nucleases. The effectiveness of these oligodeoxynucleotides was evaluated in terms of inhibition of synthesis of midkine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 45 publications
(51 reference statements)
0
51
0
Order By: Relevance
“…These activities include transforming, migrating, fibrinolytic, mitogenic, antiapoptotic, and angiogenic ones (Kojima et al, 1995;Choudhuri et al, 1997;Kadomatsu et al, 1997;Qi et al, 2000Qi et al, , 2001. Furthermore, we recently succeeded in suppressing tumour growth by using antisense MK oligodeoxyribonucleotide (Takei et al, 2001(Takei et al, , 2002. Thus, ablation of MK production or disruption of its signalling pathway could be a strong means of curing neuroblastomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities include transforming, migrating, fibrinolytic, mitogenic, antiapoptotic, and angiogenic ones (Kojima et al, 1995;Choudhuri et al, 1997;Kadomatsu et al, 1997;Qi et al, 2000Qi et al, , 2001. Furthermore, we recently succeeded in suppressing tumour growth by using antisense MK oligodeoxyribonucleotide (Takei et al, 2001(Takei et al, , 2002. Thus, ablation of MK production or disruption of its signalling pathway could be a strong means of curing neuroblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…MK transforms NIH3T3 cells , enhances fibrinolysis (Kojima et al, 1995), and promotes cell growth (Muramatsu and Muramatsu, 1991;Muramatsu et al, 1993;Takei et al, 2001), cell survival (Qi et al, 2000), cell migration (Takada et al, 1997;Maeda et al, 1999;Horiba et al, 2000;Qi et al, 2001), and angiogenesis (Choudhuri et al, 1997). MK antisense oligodeoxyribonucleotide suppresses tumour progression in nude mice (Takei et al, 2001(Takei et al, , 2002.…”
mentioning
confidence: 99%
“…(13,14) MK is barely detectable in normal adult tissues. Furthermore, the present study has established that high blood MK level is closely related to poor prognosis, at least in NBL.…”
Section: Discussionmentioning
confidence: 99%
“…(11,12) Knockdown of MK expression leads to suppression of xenografted tumors of mouse colorectal cancer cells and human prostate cancer cells. (13,14) We previously reported that the plasma MK level was correlated with the values of established prognostic factors through a study of 220 cases, including 82 non-mass-screening (sporadic) cases and 122 mass-screening cases. (15) However, in that study, information on the prognosis of patients was too limited to determine whether the plasma MK level could be a prognostic factor.…”
mentioning
confidence: 99%
“…For calculation of the half-life of each siRNA in serum, all bands were analyzed with an imaging densitometer (GelDoc 1000 system, Bio-Rad) as reported previously (26).…”
Section: Northern Blot Analysismentioning
confidence: 99%